Upsetting composition commonplaces - Barnard, Ian, 1960- (Boulder, Colorado : Utah State University Press, 2014)
In Upsetting Composition Commonplaces, Ian Barnard argues that composition still retains the bulk of instructional practices that were used in the decades before poststructuralist theory discredited them. While acknowledging that some of the foundational insights of poststructuralist theory can be difficult to translate to the classroom, Barnard upends several especially intransigent tenets that continue to influence the teaching of writing and how students are encouraged to understand writing. Using six major principles of writing classrooms and textbooks-clarity, intent, voice, ethnography, a.
Acknowledgments; Chapter 1. Introduction: For Theory's Sake; Chapter 2. Clarity; Chapter 3. Intent; Chapter 4. Voice; Chapter 5. Ethnography; Chapter 6. Audience; Chapter 7. Objectivity; Chapter 8. Conclusion: Unbecoming Institutions; Appendix; References; About the Author; Index.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: English language -- Rhetoric -- Study and teaching (Higher); English language -- Composition and exercises; Anglais (Langue) -- Composition et exercices; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; English language -- Composition and exercises; English language -- Rhetoric -- Study and teaching (Higher); Electronic book